Understanding Mixture of Experts (MoE): A Deep Dive into Scalable AI Architecture - Vasudev Daruvuri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article delves into the Mixture of Experts (MoE) architecture, a revolutionary approach to building scalable artificial intelligence systems. The article examines how MoE departs from traditional monolithic neural networks by employing multiple specialized experts and dynamic routing mechanisms. Through analysis of various implementations and applications, the article demonstrates MoE’s effectiveness in achieving computational efficiency, handling diverse tasks, and maintaining performance while reducing resource requirements. The investigation covers the fundamental architecture, gating mechanisms, technical implementation challenges, and real-world applications across domains including language processing, computer vision, and medical imaging. The article also addresses critical aspects of training complexity, load balancing strategies, and future directions in automated architecture search and efficient training methods.